Vaccination as a means of disease prevention in HIV infected individuals; successes, challenges & opportunities - SADLIER, CORINNA MARGARET (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2017)
This thesis is structured to systemically assess susceptibility to vaccine preventable infections in HIV-infected adults, to investigate effectiveness of an integrated vaccine programme as a model of care for vaccine delivery to a HIV-infected cohort, to investigate the burden of vaccine preventable infections (pneumococcal and human papillomavirus (HPV) infection) in HIV-infected adults and to assess immunognenicity of a prime-boost pneumococcal vaccine strategy and HPV vaccine in HIV-infected adults. Chapter 2 investigates seroepidemiology of common vaccine preventable infections (hepatitis A virus (HAV), hepatitis B virus (HBV), varicella zoster virus (VZV), measles, mumps and rubella (MMR) in HIV-infected adults attending the department of Genito Urinary Medicine and Infectious Diseases clinic (GUIDE), the largest tertiary referral HIV specialist centre in Ireland. Chapter 3 investigates the effectiveness of an integrated vaccine unit as a model of care for delivery of routine immunisations including seasonal influenza vaccine, pneumococcal vaccine and HBV vaccine to a cohort of HIV-infected adults. Chapter 4 examines the burden of invasive pneumococcal disease (IPD) in HIV-infected adults attending a tertiary referral hospital (St James?s Hospital, Dublin). We then investigate immunogenicity of pneumococcal vaccine strategies in HIV-infected adults. Chapter 5 examines the burden of anal cancer in HIV-infected adults attending the GUIDE clinic. Additionally, we investigate prevalence and persistence of HPV infection and infection with high-risk (hr) or oncogenic HPV types in HIV-infected MSM. We examine acceptability of HPV vaccine in this patient group and immunogenicity of the quadrivalent HPV vaccine in young HIV-infected MSM in whom the HPV vaccine is indicated. Chapter 6 extends the context surrounding the research questions, discusses the main findings of the PhD, draws conclusions and alludes to future directions of research to build on findings of this thesis.
APPROVED
Keywords: HIV infection; HPV infection; Pneumococcal infection; Vaccination